Conversion of biomass blends (walnut shell and pearl millet) for the production of solid biofuel via torrefaction under different conditions. (May 2022) - Abdullah, Iqra; Ahmad, Nabeel; Hussain, Murid; Ahmed, Ashfaq; Ahmed, Usama; Park, Young-Kwon
Abstract: The torrefaction of lignocellulose biomass was conducted to produce biochar with properties compatible with coal. Two lignocellulose biomasses, pearl millet (PM) and walnut shell (WS), were torrefied at different process temperatures (230–300 °C), residence times (30–90 min), and different compositional biomass blends to improve the characteristics of the biochar product. The resulting biochar product exhibited favorable changes in their properties. The pure biomasses and their blends obtained a high biochar yield (41–91%). The gross calorific value (GCV) ranged from 22 to 27 MJ/kg, showing an increase of 22–59% compared to the raw biomass. The torrefaction temperature had the most notable effect on the biochar quantity and quality. The biochar samples obtained from the torrefaction of different blends showed a higher GCV and other physicochemical characteristics than the pure biomasses. Scanning electron microscopy showed that these products might also be used for other applications. Graphical abstract: Image 1 Highlights: Walnut shell and pearl millet blends were converted to biochar via torrefaction. 41-91 wt% of biochar yield was obtained under different conditions. The calorific values of raw biomasses were increased from 17 to 27 MJ/kg. Produced biochar was characterized using different analytical techniques.